ARID2, a rare cause of Coffin‐Siris syndrome: A novel microdeletion at 12q12q13.11 causing severe short stature and literature review. Issue 5 (9th February 2023) - Xia, Dan; Deng, Shuyun; Gao, Chenchen; Li, Xiaojuan; Zhang, Lina; Xiao, Xiaoqin; Peng, Xiaofang; Zhang, Jieming; He, Zhanwen; Meng, Zhe; Liu, Zulin; Ouyang, Nengtai; et al.
Abstract: Coffin–Siris syndrome (CSS) 6 is caused by heterozygous pathogenic variants in the AT‐rich interaction domain 2 ( ARID2 ) gene on 12q12. Currently, only 26 cases with both detailed clinical and genetic information have been documented in the literature. Microdeletions of the entire ARID2 gene are rare. In this study, we report a 5‐year‐7‐month‐old Chinese female who underwent whole‐exome sequencing to discover that she had a de novo 1.563 Mb heterozygous copy number loss at 12q12q13.11, involving an entire deletion of ARID2 . The female had severe short stature with obvious dysmorphic facial features, global developmental delay and hypoplastic fingers and toes. Her growth hormone level was normal, with reduced IGF‐1 and increased CA19‐9 levels. After a review of the 27 patients with ARID2 deficiency, a significant positive correlation was observed between age and height standard deviation score (SDS) (r = 0.71, p  = 0.0002), suggesting a possibility of growth catch‐up. This study expands the genetic and phenotypic spectrum of CCS6 and provides a decision‐making reference for growth hormone therapy.